Inner Well-Being and Meaning-Making: Toward a Theological Anthropology of Spiritual Counseling - Innawati Teddywono; Freddy Teng (Jurnal Theologia, 2026)
This study examines the integration of humanistic principles in spiritual counseling, focusing on the lived experiences of clients and counselors as the unit of analysis. It aims to explore how empathy, unconditional acceptance, and authentic therapeutic relationships are practiced in spiritual counseling, and how these elements shape clients’ inner well-being and meaning-making processes. Using a qualitative case study design, data were collected from 10 clients and 5 spiritual counselors through semi-structured in-depth interviews, limited observations, and reflective documents. The data were analyzed using thematic analysis to identify patterns in emotional, relational, and spiritual experiences. The findings reveal that humanistic spiritual counseling facilitates a reconfiguration of inner well-being, shifting clients’ perspectives from problem-centered and normative interpretations toward reflective self-understanding, acceptance of vulnerability, and spiritual connectedness. A key novelty of this study lies in demonstrating that therapeutic relationships function as the primary relational mechanism through which psychological and spiritual dimensions are integrated. The study also highlights how clients renegotiate their sense of self and meaning within contemporary contexts influenced by digital life. This research contributes to counseling scholarship by offering an empirically grounded, relational framework for integrating humanistic and spiritual approaches to promote holistic inner well-being.